2006
DOI: 10.1140/epjb/e2006-00253-3
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature behaviour of average structure and vibrational density of states in the ternary superionic compound AgCuSe

Abstract: Abstract.Results of simultaneous thermal analysis (STA), synchrotron powder diffraction (in the range 300-973 K) and inelastic neutron scattering (at 285 and 505 K) on non-superionic β-and superionic α-AgCuSe are reported. The sample is stable in argon on heating. The volume change at the superionic phase transition is about 5%. A model for the average structure of α-AgCuSe is proposed. No anomalies in the temperature dependence of the parameters of the average structure were revealed. Ionic conductivity in α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 24 publications
6
23
0
Order By: Relevance
“…Taking this into account, we suggest a correlation between the results of the electrochemical measurements from Kadrgulov et al [3], which revealed only a relatively modest increase in the ionic conductivity with temperature within fcc-(Ag x Cu 1-x ) 2 S, and our diffraction results, which show no pronounced cation redistribution. The same correlation was supposed for related superionic fcc-AgCuSe [19], fcc-AgCuS [21] and fcc-(AgI) x -(PbI 2 ) 1-x with x= 5 4 and 3 2 [17]. Doubtless, single crystal measurements of superionic bcc-and fcc-Ag 3 CuS 2 would provide more information about the underlying structure.…”
Section: Bcc-ag 3 Cusmentioning
confidence: 58%
See 2 more Smart Citations
“…Taking this into account, we suggest a correlation between the results of the electrochemical measurements from Kadrgulov et al [3], which revealed only a relatively modest increase in the ionic conductivity with temperature within fcc-(Ag x Cu 1-x ) 2 S, and our diffraction results, which show no pronounced cation redistribution. The same correlation was supposed for related superionic fcc-AgCuSe [19], fcc-AgCuS [21] and fcc-(AgI) x -(PbI 2 ) 1-x with x= 5 4 and 3 2 [17]. Doubtless, single crystal measurements of superionic bcc-and fcc-Ag 3 CuS 2 would provide more information about the underlying structure.…”
Section: Bcc-ag 3 Cusmentioning
confidence: 58%
“…Such a nonlinearity implies that the Debye phonon model with its cubic dependence on temperature does not match the data for both compounds even at low temperatures. The non-Debye-like behaviour, which is an evidence of a high level of anharmonicity in the system, was also revealed for related eucairite (AgCuSe) [19]. An interpolation of the experimental heat capacity data yields the thermodynamic standard value ).…”
Section: Specific Heat Capacitymentioning
confidence: 73%
See 1 more Smart Citation
“…Due to the uncertain Lorenz number (L) and its temperature dependence, accurately separating the lattice thermal conductivity (κ L ) from the total κ of β-CuAgSebased samples is quite difficult. Actually, as a result of the inherent complex crystal structure and atomic-lattice disorder, the κ L of stoichiometric β-CuAgSe is already very low, about 0.1-0.5 Wm -1 K -1 , 9,10,13 close to the minimum κ L in solids. 25,26,27 Thus, the κ L reduction caused by Te-doping might be very tiny and all Te-doped samples might possess similar κ L values.…”
Section: Resultsmentioning
confidence: 99%
“…14,16 It has two phases: a high-temperature a-phase and lowtemperature b-phase. 30 Similar to Ag 2 Se, it belongs to the orthorhombic crystal structure, but different from that of the low temperature structure of Cu 2 Se, it is monoclinic or triclinic, as reported in the recent literature. 29 The lowtemperature b-CuAgSe is stable up to about 480 K and has a layered structure with low symmetry.…”
Section: Introductionmentioning
confidence: 83%